Fast disparity estimation for 3DTV applications - Yu-Cheng Tseng; Tian-Sheuan Chang (2012 Visual Communications and Image Processing, 2012)
The depth estimation reference software (DERS) algorithm developed by the MPEG 3-D Video Coding could produce high-quality disparity maps for 3DTV applications but suffers from high computational complexity due to its complicated graph-cut optimization. Therefore, this paper proposed a new fast disparity estimation algorithm that could significantly reduce the computational complexity by the downsampled matching cost method. To address the temporal consistency in videos, this paper proposed the no-motion registration for the foreground copy artifact and the still-edge preservation for the flicker artifact. In addition, the occlusion problem is also solved in the proposed algorithm. The experimental results show that our algorithm could generate comparable disparity maps to the DERS algorithm, and only takes 10.8% of its execution time.